How are Juvenile Crime and Nighttime Street Crime Affected by the Spread of Negative Trends on Social Media in Indonesia? - Apriyanto, Apriyanto; Setiawati, Rahmi; Nurhasanah, Dila Padila (Westscience Press, 2025)
This study examines the impact of negative social media trends on juvenile and street crime in Indonesia, focusing on the behaviors and motivations of adolescents influenced by online content. Using qualitative analysis, data were collected through interviews with five informants, including social media analysts, law enforcement officials, community leaders, and adolescents. The findings reveal that social media trends often glorify risky and criminal behaviors, which are further amplified by peer pressure and group dynamics. Nighttime settings, coupled with a lack of recreational alternatives, exacerbate the issue by creating opportunities for crime. Additionally, the lack of digital literacy among youth contributes to their susceptibility to harmful content. This study highlights the urgent need for digital literacy education, community engagement, and policy interventions to mitigate the influence of negative trends on social media and reduce juvenile crime in Indonesia.